La santé globale au prisme de l'analyse des politiques publiques - Gardon, Sébastien (éditions Quae, 2020)
This book links public policy analysis and questions revolving around public health, notably the public health challenges facing animal and crop production. The cases presented relate to historical issues (health crises, territorial networking of health management, the profession of veterinary medicine, animal protection) and issues that services must contend with (new public management, human-animal relations, environmental challenges).